Impact of BNT162b2 mRNA Vaccination on the Development of Short and Long-Term Vaccine-Related Adverse Events in Inflammatory Bowel Disease: A Multi-Center Prospective Study - Shehab, Mohammad; Alrashed, Fatema; Abdullah, Israa; Alfadhli, Ahmad; Ali, Hamad; Abu-Farha, Mohamed; Channanath, Arshad Mohamed; Abubaker, Jehad Ahmed; Al-Mulla, Fahd (Frontiers in Medicine, 2022)
Abstract Introduction SARS-CoV-2 vaccination has been effective in protecting against severe COVID-19 infections and related mortality. It is recommended for all individuals including patients with inflammatory bowel disease (IBD). However, safety data is lacking in this group of patients. Therefore, we aim to evaluate the short- and long-term vaccine related adverse events (AEs) in patients with IBD. Method This is a prospective, observational cohort study investigating short- and long-term AEs related to BNT162b2 vaccine in patients with IBD (study group) after first and second dose compared to healthy participants (study group). Patients were recruited at the time of attendance to clinic or infusion rooms. Short term (<3 weeks) localized and systemic AEs were assessed via questionnaire. Follow-up phone-based survey was made to collect data on long term (up to 24 weeks) AEs. Results A total of 408 patients answered the questionnaires, 204 patients in each group, the study and control group. No serious adverse events were reported in either the study nor the control group after the first or the second dose. Participants in the control group reported more frequent pain at the injection site than those in the study group after the first dose (58 (57%) vs 38 (37%) respectively, P-value= 0.005). After the second dose, tiredness was reported more frequently in the control group [49 (48%)] compared to the study group [25 (24%), (P-value<0.001)]. At 20-24 weeks post vaccination, 386 out of 408 (94.6%) patients were willing to participate in the follow-up phone based questionnaire (196 (96.1%) in the study group vs 190 (93.1%) in the control group). In both groups, none of the patients reported local, systemic or severe adverse events (0 out of 386) at week 20-244 post second dose. Conclusion The BNT162b2 vaccine is safe in patients with IBD. No severe or long-term adverse events were reported in our study. The frequency of local and systemic adverse events after the second dose was generally higher among healthy participants compared to patients with IBD. Further studies including a larger cohort with longer follow-up duration are needed to assess for possible rare adverse events.